Ligation of the Maxillary Artery Prior to Caudal Maxillectomy in the Dog—A Description of the Technique, Retrospective Evaluation of Blood Loss, and Cadaveric Evaluation of Maxillary Artery Anatomy - Carroll, Kenneth A.; Mathews, Kyle G. (Frontiers in Veterinary Science, 2020)
Two different surgical techniques have been described for performing caudal maxillectomies in dogs including the intraoral (IO) and combined dorsolateral and intraoral (DL-IO) approach. Hemorrhage is the most common intraoperative complication reported during these procedures as maxillary arterial ligation is not performed until after all osteotomies and mobilization of tumor-bearing bone. The objectives of this study were to describe a modified approach for caudal maxillectomy in the dog involving preligation of the maxillary artery, to retrospectively evaluate the ability of this modified approach to limit hemorrhage in a cohort of 22 dogs, and to clarify the vascular anatomy of the maxillary artery and its branches in relation to associated nerves. Medical records were retrospectively reviewed for cases that had caudal maxillectomy via a combined approach (with or without preligation of the maxillary artery) from January 1, 2004 to December 31, 2019. Twenty-two cases were identified, 6 without, and 16 with arterial preligation, respectively. Osteotomies were completed with a high-speed handpiece and rotary bur (n = 18), or oscillating bone saw (n = 4). All 6 (100%) dogs in the traditional DL-IO group developed hypotension under general anesthesia. Four (67%) of these required intraoperative blood transfusions, one of which required an additional postoperative blood transfusion. In contrast, only 1 of 16 (6%) dogs in the modified DL-IO group required an intraoperative blood transfusion, and only 3 (19%) developed hypotension. Moreover, a significant association was detected between postoperative PCV and the two different surgical approaches (P = 0.021). These results demonstrate the effectiveness of preligation of the maxillary artery in preventing hemorrhage in caudal maxillectomies in dogs and this represents an improvement in outcome over previously reported studies. Decreased intraoperative hemorrhage may improve surgical exposure and decrease overall patient morbidity.